Analysis of Sharia Economic Law on Buying and Selling Transactions in The Social Context (The Implementation of The Istishna Contract) - Enceng, Enceng Iip Syaripudin; Sasa Sunarsa; Gini Gaussian; Ah. Fathonih; Deni Kon Kon Furkony (Social Impact Journal, 2024)
Abstract Buying and selling is one of the forms of mumalah allowed based on the Qu'ran, Al-Hadith, and Ijma of the Ulama. To obtain goods and simultaneously sell them, it is necessary to have an Akad, this study aims to analyze the perspective of sharia economic law on buying and selling transactions in the social context through the implementation of the Istishna contract. Within the framework of Islamic law, buying and selling transactions have an important social dimension to note. Akad Istishna' is a form of transaction that can be used in a social context, where buyers and sellers interact with each other with the aim of achieving welfare and social justice. This study uses an analytical approach of Islamic economic law to understand the legal basis, legal requirements, and social implications of buying and selling transactions through the Istishna contract. The results showed that the implementation of the Istishna contract in buying and selling transactions can make a positive contribution in achieving socio-economic goals in Islam, such as wealth redistribution and community empowerment. However, it is important to ensure that the execution of the Istishna' contract is carried out in compliance with the provisions of Islamic law and the principles of social justice. This research provides valuable insights for practitioners and academics in understanding the relevance and social implications of buying and selling transactions using Istishna' contracts in the context of Islamic economic law.